2006
DOI: 10.1620/tjem.209.303
|View full text |Cite
|
Sign up to set email alerts
|

Dantrolene, a Calcium-Induced Calcium Release Inhibitor, Prevents the Acquisition of Amygdaloid Kindling in Rats, a Model of Experimental Epilepsy

Abstract: Kindling phenomenon (an experimental model of acquired epilepsy) and long-term potentiation (LTP) have many features in common. LTP is associated with an increase in intracellular Ca 2+ concentration where intracellular Ca 2+ stores play an important role. Dantrolene has an inhibitory action against Ca 2+ release from intracellular Ca 2+ stores. This substance has been reported to inhibit the induction of LTP. We investigated whether or not the development of kindling would be inhibited by dantrolene. We first… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 28 publications
1
4
0
Order By: Relevance
“…It has been demonstrated that animals pre-treated with dantrolene require significantly greater stimuli to generate seizures (Yoshida & Sakai, 2006). Moreover, after the animals are kindled, during the chronic phase of epilepsy, dantrolene has no anti-convulsant effects (Kulak et al, 2004;Yoshida & Sakai, 2006). In agreement with this, our studies have shown that dantrolene does not block SREDs when administered after in vitro SE.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…It has been demonstrated that animals pre-treated with dantrolene require significantly greater stimuli to generate seizures (Yoshida & Sakai, 2006). Moreover, after the animals are kindled, during the chronic phase of epilepsy, dantrolene has no anti-convulsant effects (Kulak et al, 2004;Yoshida & Sakai, 2006). In agreement with this, our studies have shown that dantrolene does not block SREDs when administered after in vitro SE.…”
Section: Discussionsupporting
confidence: 84%
“…Moreover, after the animals are kindled, during the chronic phase of epilepsy, dantrolene has no anti‐convulsant effects (Kulak et al. , 2004; Yoshida & Sakai, 2006). In agreement with this, our studies have shown that dantrolene does not block SREDs when administered after in vitro SE.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of regions resistant to injury had large increases of [Ca 2+ ] i even at the adult age such as the dorsal blade of the dentate gyrus and dorsal preoptic nucleus further suggesting that elevated Ca 2+ is not always correlated with cell death. While rises in Ca 2+ may lead to seizure‐induced injury, release from intracellular stores is also required for seizure propagation which may explain why elevations herein were observed in a variety of limbic structures as early as 5 h in the absence of cell death (Yoshida and Sakai, 2006).…”
Section: Discussionmentioning
confidence: 91%
“…Chemically, DTN is a derivative of hydantoin like phenytoin, but its anti‐epileptic activity is contradictory 1 . Previous studies supported the anti‐epileptic effects of DTN in animal model studies by inhibiting epileptogenesis 2,3 . A recent experimental study revealed that DTN reduces the risk of epilepsy after hippocampal neurodegeneration 4 .…”
Section: Introductionmentioning
confidence: 99%